Barriers and facilitators to epilepsy self-management for patients with physical and psychological co-morbidity. (September 2017) - Perzynski, Adam T; Ramsey, Riane K; Colón-Zimmermann, Kari; Cage, Jamie; Welter, Elisabeth; Sajatovic, Martha
Objectives: This exploratory study identifies barriers and facilitators to self-management to inform future epilepsy self-management interventions for persons who have epilepsy complicated by co-morbid mental health conditions and serious medical events. Methods: Focus group methods were used in a series of community advisory board meetings. Analysis was conducted using a thematic, constant comparative approach aiming to describe the range of barriers and facilitators salient to participants. There were a total of 22 participants, including 8 health professionals, 9 patients with epilepsy, and 5 care partners. Mean age was 49.1 (SD = 11.0, range 32–69), 11 (50%) were female, and 11 (50%) were male. For those with epilepsy, mean years having epilepsy was 24.7 (SD = 19.9, range 1–58 years). Results: Individual psychological barriers (mental illness, fatigue, and psychological distress) prominently interfered with health behaviors. Community and family barriers included stigma, lack of epilepsy knowledge, and poor social support. Facilitators included planning for seizures, learning about medications, stress management, socializing with others, and talking with other epilepsy patients. Discussion: Qualitative evidence in this study suggests a linkage between social integration and positive health behaviors. Future efforts to embed patients with epilepsy and their caregivers into clinical care processes could offset barriers and enhance facilitators.